Assessing short-term economic consequences of cow-calf contact systems in dairy production using a stochastic partial budgeting approach - Alvåsen, Karin; Haskell, Marie J.; Ivemeyer, Silvia; Eriksson, Hanna; Bicknell, Kathryn; Fall, Nils; Ahmed, Haseeb (Frontiers in Animal Science, 2023)
While early separation of dairy calves after birth has been debated from an ethical and animal welfare lens, the economic evidence surrounding alternative cow-calf contact (CCC) systems is scarce. To address this knowledge gap, we assessed the economic consequences of CCC systems using data from the Agriwise database as well as parameters from published literature in a stochastic partial budget model. The implementation of CCC is very diverse between farms, so in our study we therefore selected a limited number of CCC systems to assess. The examined CCC systems were: (i) dam rearing with limited contact at milking (15 minutes twice a day for 115 days) with no manual milk feeding; (ii) dam rearing with 21-day full contact, after which calves are manually fed 8 kg of whole milk for 94 days; and (iii) mixed calf rearing with using both dams and foster cows with full contact; calves are initially kept with their dams and then moved to foster cows at 9 days of age. We found that adoption of CCC systems was associated with decreases in contribution margins in the range of 1 to 5.4%, as compared to a rearing system where the calves were separated from their dams after one day and were manually fed 8 kg of milk for 12 weeks. These results illustrated that the costs associated with CCC systems may be fairly high under certain circumstances and may prohibit farmers from adopting this practice. Sensitivity analysis suggested that differences in milk sales, assumptions on changes in labor requirements, and changes in daily calf weight gain depending on CCC system were the main variables that governed the net impact on the contribution margins. We did not include building costs in the analyses assuming that barn structures may not change in the This is a provisional file, not the final typeset article short-term. The study focused only on short-term pecuniary associations between changes in CCC systems and contribution margins. To strengthen the economic decision-making around CCC systems, future research should consider non-monetary impacts of different CCC systems, as well as long-term economic impacts of these production strategies.